Co-operative structures in global business : communicating, transferring knowledge and learning across the corporate frontier - Boyce, Gordon, 1954- (Routledge international studies in business history ;, 2001)
This volume explores how firms operating in industries as diverse as film making, shipping, engineering, mining, and advertising have collaborated to develop innovative services, technologies and products to reach new markets.